Neuroprotective Effects of Deproteinized Calf Serum in Ischemic Stroke - Li, Weiwei; Guo, Anchen; Sun, Ming; Wang, Jiachuan; Wang, Qun (Frontiers in Neurology, 2021)
Deproteinized calf serum (DCS) may have neuroprotective effects in patients after ischemic stroke and in animal models of cerebral ischemia. The aim of this study is investigating whether and how the DCS inhibits neuronal injury following by cerebral ischemia. In Rats subjected to MCAO model, neurological deficiency score and infarct volume were lower in DCS-treated rats than in vehicle-treated rats (p<0.0005). In cultured neurons model, cell viability was decreased and apoptosis was increased by OGD/R (p<0.0005), these effects of OGD/R were attenuated by 0.4 µg/µL DCS (p<0.05) which were validated by CCK8 cell viability assay, PE-Annexin V Apoptosis Detection assay and TUNEL assay. Furthermore, the increase of intracellular ROS level in cultured neurons was suppressed by DCS (p<0.05), up-regulation of apoptotic protein Bax and the down- regulation of anti-apoptotic protein BCL-2 caused by OGD/R were revised as well. Overall, the neuroprotective effects of DCS following cerebral ischemia may in part be due to decreased ROS production and inhibition of apoptosis.